PENGEMBANGAN DESA WISATA KENDRAN SEBAGAI DAYA TARIK WISATA DI KECAMATAN TEGALALANG - Agung Sri Sulistyawati (Jurnal Ilmiah Hospitality Management, 2010)
Every village, mainly villages in Bali must have a unique and distinctive charm. Great potential and natural beauty found in the village of Kendran can be used to support tourism. The purpose of this study was to find out what the tourism potential that is owned by Village Kendran as rural tourism and what are the attractions that can be developed as a tourist attraction. The results showed that the Village Kendran have tourism potential, both physical and non-physical to be developed as tourist villages. With the SWOT approach, gained some strategies for the development of the Village attractions Kendran as rural tourism, among others: developing nature tourism, cultural, and spiritual maximally; increase cooperation between the village and the central government in the provision of tourism facilities and infrastructure; establishing programs tourism village to village Kendran; develop tracking paths that can be used by tourists; develop people's homes to become homestay; build public facilities such as toilets, etc..; formed a partnership with the travel agents or Travel Bureau (BPW); maintain authenticity natural village as an identity that becomes the main potential; raise awareness of rural youth to preserve the culture; improve promotion to introduce the Village Kendran; conduct training for villagers, especially in the field of tourism and foreign languages. From some of the strategy, eventually generate tourism village programs, such as: (1) Cultural Art Lesson, in which there is Dance, Painting, and the Statue Carving Lesson, (2) Traditional Game Program, (3) Village Tour Program, ( 4) Farm Lesson, (5) Yoga and Meditation Program, (6) Puppet Show Every Purnama and Tilem, (7) Temple Tour, (8) Outing Program, (9) Rice Tracking, (10) Cycling Tour, (11) Cooking Lesson, and (12) Majejahitan Lesson. Some things that can be suggested is for the government, village government, local government, or the central government soon designing and establishing programs or a tour package which will be held in the Village Kendran as a tourist village, Gianyar regency government along with the village authorities to immediately make improvements and Kendran Village development that have tourism facilities and infrastructures are fit for use by tourists